Fishing safely during COVID-19 in Newfoundland and Labrador, Canada: Making it happen. (November 2022) - Neis, Barbara; López Gómez, María Andrée; Reid-Musson, Emily; Greenslade, Brenda; Decker, David; Finnis, Joel; Knott, Christine
Abstract: Globally, fisheries have been the site of multiple documented outbreaks of COVID-19. Existing studies point to the threat posed by the pandemic to livelihoods and health among migrant industrial fishery workers, small-scale fish harvesters, and fishing communities. They show the pandemic enhanced safety, economic, social and political layers of vulnerability in fisheries, while also showcasing examples of resilience. Case studies of COVID-19 response provide an opportunity to explore how existing organizational structures, leadership and networks in fisheries can enable the rapid co-development of customized strategies for fishing safely during large-scale global disruptions such as pandemics. This article contributes to our understanding of governance and fishing safety in small-scale fisheries during the early pandemic, examining the response of small-scale fisheries in the Canadian province of Newfoundland and Labrador. These seasonal fisheries successfully opened with regulator approval after a short delay and operated without documented COVID-19 outbreaks during 2020. Findings draw from key informant interviews with a safety sector association and union leader, complemented with insights from an anonymous online survey of small-scale harvesters. Interviews capture the organizational processes and resources mobilized to rapidly co-develop the COVID-19 Safe Work Practice Guideline. Online survey findings indicate that fifty-nine percent of respondents (crew and skippers) had no COVID-19-related concerns while fishing in 2020; older harvesters and owner-operators were significantly more likely to indicate concerns. When asked about the relative practicality of listed COVID-19 precautions, respondents commonly identified sanitization, reduced interactions with shore workers, social distancing, protection equipment, modifications to eating/rest areas, and reduced crew as impractical. These assessments are generally consistent with those of the interviewed leaders and the Guideline approach. This suggests the co-developed Guideline provided tailored and practical COVID-19 prevention strategies. Pre-existing governance structures and networks can help address small-scale fisheries vulnerabilities to pandemics by supporting co-development of organizational resources and evidence-informed prevention strategies. Highlights: The COVID-19 pandemic is a serious economic, social and health threat to fisheries globally. There is a lack of health and safety information around COVID-19 tailored to the needs of small-scale fisheries. This paper presents a case study of the lCOVID-19 response among small-scale harvesters in Newfoundland and Labrador, Canada. Findings provide insight into governance processes with the potential to address small-scale fishery health and safety concerns for this and future pandemics.